Business-to-business marketing communications : value and efficiency considerations in recessionary times - Rizomyliotis, Ioannis; Konstantoulaki, Kleopatra; Kostopoulos, Ioannis (Palgrave Macmillan, 2017)
This book addresses the rapidly changing Business-to-Business (B2B) marketing communication landscape, in particular the shrinking of marketing budgets and the increasing demand for measurable results. Despite the rapid drop of print media usage, the authors suggest the need for increased accountability for the use of advertising media and highlight ways to boost effectiveness. The book provides a robust analysis of the current B2B environment along with a research-informed illustration of the future. Aiming to fill a gap in existing literature and offer new research findings, this study offers a comprehensive guide to assist practitioners in decision-making and a stimulating analysis of the B2B marketing communications landscape which will be of great interest to academics of marketing and communications.